Revisión al sustento epistemológico de la pedagogía y sus aportes a la educación literaria en América Latina - Carrera Barragán, Diego Andrés (2022)
This research reviews the Epistemological Support of Pedagogy that determines its scientificity, including contemporary research contributions, to identify their contributions to Literary Education in Latin America. For this purpose, a descriptive documentary review was carried out under a transversal bibliographic design that used documentary compilation and the hermeneutic method for collecting and interpreting information, respectively. The results of the study are presented in three categories designed according to the specific objectives: Academic production of pedagogy as a science, Academic production in Literary Education: Characterization of the role of Pedagogy and its scope in literary education, and Contribution of the Epistemological Statute of Pedagogy to Literary Education. In the first category, the substantial guidelines of the theoretical support that validates the scientificity of Pedagogy are evidenced. In the second, it is revealed how the epistemic status of Pedagogy is present and how it is considered in the theoretical sections of the research referred to in the field of Literary Education. Finally, the third category details the contributions of the statute to literary education using tables with criteria supported by textual quotations found in the articles studied.